I have a two part problem that is giving me a lot of trouble. Mostly because the rules I would have used to solve these two are ruled out.
Problem - Use propositional logic to prove the following:
Part 1 - (Don't use exportation rule of inference)
[(P ^ Q) -> R)] -> [P -> (Q -> R)]
I've got
(P ^ Q) -> R) hyp
Part 2 - (Don't use contraposition rule of inference)
(P -> Q) -> (Q' -> P')
I've got
(P -> Q) hyp
P' v Q 1, imp
Any suggestions / help would be much appreciated. Thanks in advance!
Problem - Use propositional logic to prove the following:
Part 1 - (Don't use exportation rule of inference)
[(P ^ Q) -> R)] -> [P -> (Q -> R)]
I've got
(P ^ Q) -> R) hyp
Part 2 - (Don't use contraposition rule of inference)
(P -> Q) -> (Q' -> P')
I've got
(P -> Q) hyp
P' v Q 1, imp
Any suggestions / help would be much appreciated. Thanks in advance!